Kidney Function Test of Female Wistar Rat (Rattus norvegicus Berkenhout, 1769) of Subchronic Toxicity Test of Arthrospira maxima and Chlorella vulgaris - Mulyati Mulyati; Anita Yuliana; Slamet Widiyanto (Universitas Gadjah Mada, 2019)
Arthrospira maxima and Chlorella vulgaris are contained a high protein and antioxidant levels that can be used as functional foods or supplements to improve health. Furthermore, this material needs to be monitored for safety. The aims of this research were determined the subchronic toxicity test of microalgae A. maxima and C. vulgaris on kidney function. Parameters of this research were creatinine levels, urea levels, kidney index, and histological structure of the kidney glomerular. Besides that, the progression of body weight was observed. Five teen female Wistar rats (Rattus norvegicus Berkenhout,1769) divided into three groups randomly were one control group and two treatment groups using A. maxima and C. vulgaris in the same dose were 2500 mg/kg of body weight. Subchronic toxicity test was conducted by oral gavage every day during 90 days — the measurement of creatinine levels and urea levels on the 30th, 60th, and 90th day. Kidney index and glomerular histology of rat’s kidney was prepared after necropsy at the end of this research. Base on the results, it can be concluded that consume of Arthrospira maxima, and Chlorella vulgaris at 2500 mg/kg of body weight increased creatinine and urea levels. Bodyweight, kidney index, and pathological glomerular cells of histological kidney were still in normal value.